2015
DOI: 10.4103/0973-6247.150958
|View full text |Cite
|
Sign up to set email alerts
|

Study of red blood cell alloimmunization in multitransfused thalassemic children of Jammu region

Abstract: Introduction:Thalassemia is one of the most common genetic disorder of hemoglobin synthesis in Jammu region. Although RBC transfusion is life saving for these patients, it may be associated with some complications like RBC alloimmunization. Thus, the aim of this study was to determine the frequency of alloimmunization and the most common alloantibodies involved.Material and Methods:This was a descriptive study involving a total of 70 thalassemic patients in the age range of 2-17 years receiving regular blood t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 9 publications
3
13
0
Order By: Relevance
“…This is similar to the previous reports of alloimmunization. [62324] As is evident from these findings, antibodies against the Rh and Kell system are the most commonly implicated alloantibodies. This re-iterates the need for extended Rh and Kell phenotype-matched RBCs in patients requiring repeated transfusions to prevent RBC alloimmunization.…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to the previous reports of alloimmunization. [62324] As is evident from these findings, antibodies against the Rh and Kell system are the most commonly implicated alloantibodies. This re-iterates the need for extended Rh and Kell phenotype-matched RBCs in patients requiring repeated transfusions to prevent RBC alloimmunization.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of alloimmunization was reported as high as 23% in few countries [ 15 , 16 ] to 7.7% in some other nations [ 17 , 18 ] depending on demography and homogeneity of population. Different studies were reported from different parts of India showing the alloimmunization rate in between 3.4% and 8.6% [ 19 22 ]. In this study the rate of alloimmunization was 5.6% which was consistent with the rate of alloimmunization observed in other parts of India.…”
Section: Discussionmentioning
confidence: 99%
“…With regards to these studies it seems that alloimmunization and even autoimmunization are a major concern in transfusion dependent thalassemia patients [5,7,22]. In Iranian patients with β-thalassemia major, transfusion related reaction was reported with a prevalence of about 15% in some studies [15,20]. Sometime, in patients with alloimmunization is significant and can have lifethreatening consequences.…”
Section: Comparison Between Alloim-munization In Iran With Other Counmentioning
confidence: 99%
“…Although as low as 0.7% of autoantibody was reported in other countries, most studies reported a significantly higher incidence of autoimmunization in other countries [18,[22][23][24][25]. In Kell blood group system, the most commonly alloantibodies directed against K antigen [14,[18][19][20]. In Rh blood group system, majority of antibody directed against D, E and C antigens (Table 3).…”
Section: Comparison Between Alloim-munization In Iran With Other Counmentioning
confidence: 99%
See 1 more Smart Citation